2008
DOI: 10.1002/ajp.20535
|View full text |Cite
|
Sign up to set email alerts
|

The functions of the “Greeting Ceremony” among male mantled howlers (Alouatta palliata) on Agaltepec Island, Mexico

Abstract: Nonhuman primates use greeting behaviors as nonaggressive communicatory signals in multiple social contexts. Adult male mantled howlers (Alouatta palliata) perform a ritual greeting that has been associated with bond-strengthening functions. The aim of this study is to explore the greeting patterns of male howlers living on Agaltepec Island, Mexico. Specifically, we analyzed the relationships between greetings and several individual, relational, and contextual variables, such as the expression of affiliation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…For example, greeting signals are often produced during intragroup conflicts, either to decrease or increase levels of aggression (e.g. mantled howler monkeys, Alouatta palliata: Dias et al 2008; baboons, Papio hamadryas and P. cynocephalus : Colmenares 1990; spotted hyaenas, Crocuta crocuta: East et al 1993; spider monkeys, Ateles geoffroyi: Aureli & Schaffner 2007;Schaffner & Aureli 2005). Other reported functions have to do with assessing another individual's willingness to interact socially at that particular moment or with testing long-term bonds between familiar individuals (Guinea baboons, Papio papio: Whitham & Maestripieri 2003; black-horned capuchins, Cebus apella: Lynch Alfaro 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, greeting signals are often produced during intragroup conflicts, either to decrease or increase levels of aggression (e.g. mantled howler monkeys, Alouatta palliata: Dias et al 2008; baboons, Papio hamadryas and P. cynocephalus : Colmenares 1990; spotted hyaenas, Crocuta crocuta: East et al 1993; spider monkeys, Ateles geoffroyi: Aureli & Schaffner 2007;Schaffner & Aureli 2005). Other reported functions have to do with assessing another individual's willingness to interact socially at that particular moment or with testing long-term bonds between familiar individuals (Guinea baboons, Papio papio: Whitham & Maestripieri 2003; black-horned capuchins, Cebus apella: Lynch Alfaro 2008).…”
mentioning
confidence: 99%
“…In chimpanzees, Pan troglodytes, however, greeting is conducted in the vocal domain, the so-called 'pant-grunts' (Bygott 1979;de Waal 1982;Goodall 1986). A remarkable feature of chimpanzee pant-grunts is that the signal is given only by lower-ranking individuals when encountering a more dominant group member, which contrasts with the greeting behaviour of other primates and nonprimates, such as baboons (Colmenares 1990), howler monkeys (Dias et al 2008) or hyaenas (East et al 1993). In captive chimpanzees, pantgrunts are often accompanied by ritualized behaviours of subordination, such as bobbing, crouching or presenting (de Waal 1982).…”
mentioning
confidence: 99%
“…Such tolerance is fully compatible with the formation of male coalitions and appears to be reinforced by mutual howling (Kitchen et al 2004 ;Van Belle et al 2008 , in press) and social embracing (Wang and Milton 2003 ;Dias et al 2008 ;Garber and Kowalewski 2011 ). Compared to single males, male coalitions increase the chances of successfully taking over groups or the likelihood of resident males repelling intruding males (Sekulic 1983 ;Crockett 2003 ;Van Belle et al 2008 ).…”
Section: Intragroup Mating Patternsmentioning
confidence: 99%
“…Howler monkeys represent an instructive model for exploring the operation of sexual selection on reproductive behavior because the genus is characterized by a highly fl exible social system with all species exhibiting marked variability in group size and composition, and regardless of the species, most populations contain unimale and multimale bisexual groups . Resident males in multimale groups rarely engage in agonistic interactions (Wang and Milton 2003 ;Van Belle et al 2008 ;Rangel-Negrín et al 2011 ;Garber and Kowalewski 2011 ), and generally no clear dominance hierarchies can be discerned (but see Jones 1980 ;Dias et al 2008 ). Nevertheless, one resident male, herein referred to as the "central" male, can be recognized based on his closer spatial association with resident females, his priority of access to fertile females, and increased participation in howling bouts compared to "noncentral" males (Wang and Milton 2003 ;Kitchen et al 2004 ;Kowalewski 2007 ;Van Belle et al 2008 ).…”
Section: Sexual Selection Theory and Howler Monkeysmentioning
confidence: 99%
“…Previous studies showed in A. caraya 0.019 int/ind/hr [Bicca-Marques, 1993], and in A. palliata; male-male ¼ 0.018 int/ind/hr, male-female ¼ 0.049 int/ind/hr [Wang & Milton, 2003]. The low level of agonistic interactions is possibly related to the high costs imposed by physical aggression that may result in the death of males [Dias et al, 2010], thus, the predominant behaviors in male-male howler relationships involve low physical risk [Dias et al, 2008;Garber & Kowalewksi, 2011;Preuschoft & van Schaik, 2000;van Belle et al, 2008;Wang & Milton, 2003]. Nevertheless, intense forms of aggression have been reported for howlers (Alouatta arctoidea [Crockett & Pope, 1988], A. palliatta [Cristóbal-Azkarate et al, 2004;Dias et al, 2010]).…”
Section: Dominance and Relatednessmentioning
confidence: 99%